Analysis of The Effect of Ethical Beliefs and Accounting Literacy in Improving Self-Efficacy and Performance of MSMES - Amalia, Citra; Junaidi, Junaidi; Sahrir, Sahrir (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to determine the extent to which ethical beliefs and accounting literacy influence self-efficacy, and how self-efficacy plays a role in improving the performance of micro, small, and medium enterprises (MSMEs). A total of 105 MSME actors participated in this study by completing questionnaires. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS 22 and SPSS 22. The research findings indicate that ethical beliefs have a positive but non-significant impact on self-efficacy, while accounting literacy has a positive and significant impact on self-efficacy. Additionally, self-efficacy is proven to have a positive and significant effect on MSME performance, and self-efficacy is proven to play a positive and significant mediating role in linking ethical beliefs and accounting literacy to MSME performance. Therefore, strengthening accounting literacy and self-efficacy is a key strategy for improving MSME performance, while ethical values remain important in supporting reputation and business sustainability